The Relationship of Knowledge to The Sterilization Behavior of The Tool to Prevent Disease Transmission in Dental Health Students - Utari Murtia Dewi; Abu Hamid (Fakultas Kedokteran Universitas Sriwijaya, 2022)
When taking action in the field of dentistry, knowledge is a factor that greatly influences the operator's actions. Knowledge is the result of understanding after feeling an observed object. If their knowledge is good, their attitudes and actions will be better when carrying out sterilization. Behavior is an individual action that is observable or cannot be observed as a human interaction with the environment in the form of knowledge, attitudes and actions. The type of research in this study is an analytical survey with a cross sectional approach, the sample is level II and III students of the Department of Dental Health, Poltekkes, Ministry of Health, Palembang who will fill out a questionnaire. Analysis uses the Chi-Square test. Most students have a level of knowledge with good criteria and have behavior with good criteria. There is a significant relationship between knowledge and sterilization behavior in preventing cross infection with a p value = 0.000.